Effectiveness of Web-Based Flipped Classroom Reviewed from UnderstandingMathematics Concepts of Primary Teacher Education Students: Efektivitas Flipped Classroom Berbasis Web Ditinjau dari Pemahaman Konsep Matematika Mahasiswa Pendidikan Guru Sekolah Dasar - Ermiana, Ida; Rosyidah, Awal Nur Khalifatur; Fauzi, Asri; Hidayati, Vivi Rachmatul (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effectiveness of the web-based Flipped Classroom model in terms of understanding the mathematical concepts of PGSD students. This type of research is a quasi-experimental quantitative research with one group pretest-posttest. This research was conducted on 2nd-semester PGSD students taking Mathematics Education courses. The population of this study was all 2nd-semester PGSD students and the sample of this study was taken randomly as many as 32 students. This research instrument uses a test for understanding mathematical concepts on geometry material with a total of 10 multiple-choice questions. The data analysis techniques in this study are the normality test as a prerequisite test, the Wilcoxon test to determine the difference between the average pretest and posttest, and the effect size test (Cohen's d) to conclude that the web-based flipped classroom model is effective or not on understanding mathematical concepts. The results of this study indicate that the normality test on the pretest data obtained data with a normal distribution, but on the posttest data the data was not normally distributed, so the Wilcoxon nonparametric test was used. Wilcoxon test results show the results of sig. <0.005, which means that there is a significant average difference between the pre-test and post-test scores. Then from the results of the Effect Size test, the results of 1.55 are included in the very large category.